Long-term trends of second generation anticoagulant rodenticides (SGARs) show widespread contamination of a bird-eating predator, the Eurasian Sparrowhawk (Accipiter nisus) in Britain. (1st December 2022) - Broughton, Richard K.; Searle, Kate R.; Walker, Lee A.; Potter, Elaine D.; Pereira, M Glória; Carter, Heather; Sleep, Darren; Noble, David G.; Butler, Adam; Johnson, Andrew C.
Abstract: Second generation anticoagulant rodenticides (SGARs) are widely used to control rodents around the world. However, contamination by SGARs is detectable in many non-target species, particularly carnivorous mammals or birds-of-prey that hunt or scavenge on poisoned rodents. The SGAR trophic transfer pathway via rodents and their predators/scavengers appears widespread, but little is known of other pathways of SGAR contamination in non-target wildlife. This is despite the detection of SGARs in predators that do not eat rodents, such as specialist bird-eating hawks. We used a Bayesian modelling framework to examine the extent and spatio-temporal trends of SGAR contamination in the livers of 259 Eurasian Sparrowhawks, a specialist bird-eating raptor, in regions of Britain during 1995–2015. SGARs, predominantly difenacoum, were detected in 81% of birds, with highest concentrations in males and adults. SGAR concentrations in birds were lowest in Scotland and higher or increasing in other regions of Britain, which had a greater arable or urban land cover where SGARs may be widely deployed for rodent control. However, there was no overall trend for Britain, and 97% of SGAR residues in Eurasian Sparrowhawks were below 100 ng/g (wet weight), which is a potential threshold for lethal effects. The results have potential implications for the population decline of Eurasian Sparrowhawks in Britain. Fundamentally, the results indicate an extensive and persistent contamination of the avian trophic transfer pathway on a national scale, where bird-eating raptors and, by extension, their prey appear to be widely exposed to SGARs. Consequently, these findings have implications for wildlife contamination worldwide, wherever these common rodenticides are deployed, as widespread exposure of non-target species can apparently occur via multiple trophic transfer pathways involving birds as well as rodents. Graphical abstract: Image 1 Highlights: Second generation anticoagulant rodenticides were studied in Eurasian Sparrowhawks. 81% of British birds were contaminated, but liver concentrations were generally low. The primary rodenticide contaminant found in birds was difenacoum. Rodenticide concentrations were highest in adults and in male birds. Rodenticide concentrations were also higher in urbanised and agricultural regions.